1960
DOI: 10.1149/1.2427544
|View full text |Cite
|
Sign up to set email alerts
|

“Oxidation of Niobium in the Temperature Range 350°–750°C”[J. Electrochem. Soc., 106, 495 (1960)]

Abstract: not Available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1973
1973
1973
1973

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…In pure columbium, when the oxidation rate .nstant i ; plotted versus temperature, it has been found that for oxygen pressures above 10 torr the rate goes through a maximum around 1300 F, decreases to about 1500 F, after which it again increases with temperature. [11][12][13] In a study of that rate anomaly in binary Cb-Ta alloys 14 it was found that the oxidation rate maximum is shifted upward in temperature with increasing tantalum additions. The rate maximum was shifted to 1800 F by 30 at.% Ta with further additions having little effect on the temperature of the rate maximum.…”
Section: :'mentioning
confidence: 99%
“…In pure columbium, when the oxidation rate .nstant i ; plotted versus temperature, it has been found that for oxygen pressures above 10 torr the rate goes through a maximum around 1300 F, decreases to about 1500 F, after which it again increases with temperature. [11][12][13] In a study of that rate anomaly in binary Cb-Ta alloys 14 it was found that the oxidation rate maximum is shifted upward in temperature with increasing tantalum additions. The rate maximum was shifted to 1800 F by 30 at.% Ta with further additions having little effect on the temperature of the rate maximum.…”
Section: :'mentioning
confidence: 99%